Fabrication, characterization and cellular biocompatibility of porous biphasic calcium phosphate bioceramic scaffolds with different pore sizes. Issue 14 (1st November 2016) - Tang, Xuehui; Mao, Lixia; Liu, Jiaqiang; Yang, Zhi; Zhang, Wei; Shu, Mengjun; Hu, Nantao; Jiang, Lingyong; Fang, Bing
Abstract: Facile wet-chemical methods are applied to synthesize hydroxyapatite and β-tricalcium phosphate nanoparticles, respectively. Porous biphasic calcium phosphate (BCP) bioceramic scaffolds are then fabricated using as-prepared HA and β-tricalcium phosphate nanoparticle powders. The macro pore diameter of BCP bioceramic scaffolds can be controlled by adjusting the amount of surfactants. The average diameter of the macro pores in BCP bioceramic scaffolds increases from 100 to 600 µm with the decrease amount of sodium dodecyl sulfate from 0.8 to 0.5 g, respectively. The BCP bioceramic scaffolds gradually degrade and the calcium-phosphate compounds fully deposit when soaking in simulated body fluid solution. Moreover, The BCP bioceramic scaffolds have outstanding biocompatibility to promote the cellular growth and proliferation of human dental pulp stem cells (hDPSCs). The hDPSCs also demonstrate favorable cellular adhering capacity on the pore surface of scaffolds, especially on the scaffolds with 100–200 µm pore diameter. The porous BCP bioceramic scaffold with inter-connected pore structure, outstanding in vitro cellular biocompatibility, favorable cell viability and adhesion ability will be a promising biomaterial for bone or dentin tissue regeneration.